Pola dan Struktur Ruang Kelurahan Bulukunyi Sebagai Ibukota Kecamatan Polongbangkeng Selatan Kabupaten Takalar - Hasan, Muhammad Husain (geoedusains: Jurnal Pendidikan Geografi, 2021)
Kelurahan were a political region as level as village below the district which was governed by a lurah. In the history of its development, Kelurahan Bulukunyi had the status of a village until finally it changed its status became a kelurahan. The aim of this research were to examine the spatial structure and pattern of the Kelurahan Bulukunyi as the capital of the district in order to obtain an overview of the structure and direction of development of the region. The research method used was descriptive qualitative. Technique of data collection was triangulation with analysis of aerial imagery and field surveys. The collected data will be analyzed by descriptive qualitatively including data reduction and categorization, data display, and conclusions. The results showed: 1). Residential settlements and activity centers in Kelurahan Bulukunyi were regularly patterned or parallel to roads with development following the existence of transportation routes; 2). Sufficiently available public facilities include office facilities, health, economy, education, and worship; 4). The land used was still dominated by agricultural land used.